The Community Education and Health Examination on the Prevention of Intestinal Parasite Infections among Waste Collectors: Education and health examination among waste collectors - Heny Arwati; Ratna Wahyuni; Silvia Indah Ramadhany; Intan Pratama Purwaningrum; Yuvisha Naura Salma; Nia Ardelia; Abigail Ulil Albab; Nidzam Firlyan Eka Yuda; Muhammad Harya Abduh (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Waste collectors are at a higher risk of contracting intestinal parasites due to direct contact with waste. Purpose of the Study This community service activity aimed to educate waste collectors on the use of personal protective equipment (PPE), promote Clean and Healthy Living Behavior (CHLB), and conduct health examinations to prevent intestinal parasitic infections. Methods: Community education was conducted through lectures, along with pre-tests and post-tests, followed by interviews to assess healthy living behaviors, the use of PPE, CHLB, and history of intestinal parasite infections. Health and stool examinations to determine intestinal parasites among waste collectors. Results: The stool examination revealed the presence of the genus Blastocystis parasite.